The 'STORI' of the Rings 2014—a summary of the STORI'14 conference. (26th November 2015) - Doherty, D T; Kraft-Bermuth, S; Litvinov, S
Abstract: The 9th International Conference on Nuclear Physics at Storage Rings (STORI 2014) was held in fall 2014 in Sankt Goar, Germany. This recent conference brought together renowned experts working on, and performing experiments at, ion storage rings and ion trap facilities worldwide. This, therefore, provides an excellent opportunity to consider the present status of the field and to pinpoint some areas of interest for future work. Numerous experimental results were presented covering a diverse range of topics addressing fundamental questions in atomic and nuclear physics, ranging from cold molecules all the way to nuclear reactions in stars. In addition, technical developments for better accuracy were presented. Several new facilities are under construction or being planned across the globe. In this article we will summarize some of the key results and exciting developments presented at the conference.